English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

15 answers

Using pythagorean theorem,
(hypotenuse)^2=sum of the sqaures of the other 2 sides

therefore, 26^2=10^2+side^2
side=root(676-100)
=root(576)
=24 units

2007-01-24 03:36:38 · answer #1 · answered by purpleraiment 2 · 0 0

You can do the Pythagorean theorem, as has been done, but this is one of the special triangles.

The special ratios are 3/4/5 (leg/leg/hypotenuse) and 5/12/13.
Multiples work as well, so the 3/4/5 could be 6/8/10 or 15/20/25 and the 5/12/13 could be 10/24/26.

2007-01-24 03:43:13 · answer #2 · answered by math_prof 5 · 0 0

use the pythag theorem; a^2 + b^2 = c^2. C=the hypotenuse.
In this case,
we'd use 10^2 + b^2 (cause we're looking for a leg) = 26^2.
So, 100 + b^2 = 676.
Take 100 to the other side, so 676 - 100 = 576.
Now we have b^2 = 576. In order to find b, find the square root of 576.
The square root of 576 is 24.

The other leg measures 24.

2007-01-24 03:41:58 · answer #3 · answered by parrotdizzledoa 1 · 0 0

Use the Pythagoream Theorem which is a^2 + b^2 = c^2. If you use it turns to c^2 - a^2 = b^a where a and b are legs and c is the hypotenuse. which turns to 26^2 - 10^2 = b^2. The answer of that is 24.

2007-01-24 03:39:05 · answer #4 · answered by samatroy 2 · 0 0

a² = b² + c²
26² = 10² + c²
676 = 100 + c²
676 - 100 = c²
576 = c²
c = sqrt 576
c = 24
Ans: The other leg is 24.
><

2007-01-24 03:47:02 · answer #5 · answered by aeiou 7 · 0 0

Let a,b,c be the sides, with c the hypotenuse.
Then
c² = a² + b²
26² = 100 + b²
676 = 100 + b²
b² = 576
b = 24.

2007-01-24 04:20:34 · answer #6 · answered by steiner1745 7 · 0 0

Easy button:

Learn the Pythagorean triples.

5-12-13 is one such triple

But
5*2 - 12*2 - 13*2 is also one such triple
10 - 24 - 26

You're given the 10 & 26. The other leg is 24.

2007-01-24 03:49:30 · answer #7 · answered by bequalming 5 · 0 0

Pythagoras' Theore is that:

hyp^2 = (first leg )^2 + (second leg )^2

Just apply it to your example
26^2 = 10^2 + (other leg)^2

Just take +10^2 over to the left hand side like in a normal equation
26^2 - 10^2 = (other leg)^2

Calculate a few values
676 - 100 = (other leg)^2
576 = (other leg)^2

Now as other leg squared is 576, square root of 576 is one leg

square root of 576 = other leg


Calculate this and: other leg = 24

2007-01-24 03:41:35 · answer #8 · answered by ღ♥ღ latoya 4 · 0 0

24

2007-01-24 03:39:46 · answer #9 · answered by muskrat_h8r 2 · 0 0

use the formulae:

(hypotenuse)^2 = (side1)^2 + (side2)^2

so we have
(26)^2 = (10)^2 + x^2
=> 676 = 100 + x^2
=> x^2 = 676 - 100
=> x^2 = 576
=> x = 24

2007-01-24 03:39:21 · answer #10 · answered by Manisha 4 · 0 0

fedest.com, questions and answers